Impact of disabled circadian clock on yellow fever mosquito Aedes aegypti fitness and behaviors - Vinaya Shetty; Jacob I. Meyers; Ying Zhang; Christine Merlin; Michel A. Slotman (Scientific Reports, 2022)
Abstract Like other insects, Aedes aegypti displays strong daily patterns in host seeking and mating. Much of these behaviors are believed to be under the control of a circadian clock, an endogenous timekeeping mechanism relying on transcriptional/translational negative feedback loops that drive rhythmic physiology and behavior. To examine the connection between the circadian clock and various Ae. aegypti behaviors, we knocked out the core clock gene cycle using CRISPR/Cas9. We found that the rhythmic pattern and intensity of mRNA expression of seven circadian genes, including AeCyc −/− , were altered across the day/night cycle as well as in constant darkness conditions. We further show that the mutant CYC protein is incapable of forming a dimer with CLK to stimulate per expression and that the endogenous clock is disabled in AeCyc −/− mosquitoes. AeCyc −/− do not display the bimodal locomotor activity pattern of wild type, have a significantly reduced response to host odor, reduced egg hatching rates, delayed embryonic development and reduced adult survival and mating success. Surprisingly however, the propensity to blood feed in AeCyc −/− females is significantly higher than in wildtype females. Together with other recent work on the circadian clock control of key aspects of mosquito biology, our data on how cycle KO affects mosquito behavior and fitness provides a basis for further work into the pathways that connect the mosquito endogenous clock to its vector competence.